Correlation between stress hyperglycemic ratio and all-cause mortality in diabetic patients with heart failure - Zhenrun Zhan; Chao Lan; Yongze Zhang; Jiebin Lin; Ke Zheng; Ximei Shen; Sunjie Yan (BMC Endocrine Disorders)
Abstract Objective The stress hyperglycemia ratio (SHR) quantifies the intensity of stress hyperglycemia by highlighting the rate of change in fasting blood glucose during stress. Several studies have validated the association of SHR with poor prognosis in cardiovascular disease. However, the value of SHR in diabetic patients with severe heart failure requiring ICU admission remains unclear. The aim of this study was to investigate the predictive value of SHR for poor prognosis in diabetic patients with heart failure. Methods This study was based on the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database and included diabetic patients with a diagnosis of heart failure. The primary outcome event was all-cause mortality. Patients were grouped according to quartiles of SHR, and the association between SHR and all-cause mortality was assessed using restricted cubic spline analysis, survival analysis, and Cox proportional hazards regression analysis. Results A total of 1470 patients (55.7% male) were enrolled in this study. In-hospital mortality and intensive care unit (ICU) mortality reached 12.2% and 7.8%, respectively. In-hospital mortality was significantly higher in the highest quartile group of SHR. After correction for confounders, the risk of death was significantly higher in the highest quartile group compared with the lowest quartile group. Restricted cubic spline plot analysis showed a positive linear relationship between SHR and in-hospital and ICU mortality. Conclusion SHR was significantly associated with in-hospital and ICU all-cause mortality in severe patients. This finding suggests that SHR may be useful in identifying diabetic patients with severe heart failure at high risk for all-cause mortality.